A COMPLEX TRANSFORMATION OF A PROCESS ORGANIZATION - Igor G. Fiodorov (Открытое образование (Москва), 2016)
The article is dedicated to a transformation of an organizational structure of the organization which starts its process transformation. It is suggested, that a success of the process transformation strongly depends on the ability of a company make a complex change in an organizational structure.